Lampblack of soybean oil as a low-cost electrode material in supercapacitor application - Lawaju, Umesh; KC, Anupam; Joshi , Prakash (Scientific World, 2023)
Lampblack of soybean oil was investigated as a potential low-cost material to make electrodes of supercapacitors. The lampblack carbon was characterized using Scanning Electron Microscopy (SEM) and Energy Dispersive X-ray Spectroscopy (EDS). The electrochemical performance of the lampblack carbon electrode was tested using a three-electrode system, where a platinum wire was used as a counter electrode, a carbon electrode as a working electrode, and Ag/AgCl electrode as a reference electrode. The experiments, Galvanostatic Charge-Discharge (GCD) and Cyclic Voltammetry (CV) were performed in 3M aq. KOH. The specific capacitance of the lampblack carbon electrode from GCD was found to be 49.27 F g-1 at 1 A g-1. The lampblack carbon electrode showed good capacitive behavior at both low and high scan rates. The results indicated that lampblack carbon of soybean oil can be a new efficient alternative material for low-cost high-performance supercapacitors.